Faktor-faktor Yang Memengaruhi Persepsi Nazhir Terhadap Wakaf Uang. - Rahmat Dahlan (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2014)
Factors That Influence Nazhir Perception on Cash Waqf. The purpose of this study is to analyze what factors are influencing cash waqf perceptions of nazhir. The sampling method that used in this research is non- probability sampling with adjusted sampling technique. The method was used to analyze the data are descriptive analysisi and logistic regression. The result of this study showed that perception nazhir influenced by the media access information and understanding of waqf regulation. Nazhir that agree with cash waqf and understand with waqf regulation is about 0,94 times if we compare with the nazhir that not understand with waqf requlation. The educational background will be influence to the mindset of nazhir perception and understanding.  DOI:10.15408/aiq.v6i2.1237